Double-Stranded RNA Structural Elements Holding the Key to Translational Regulation in Cancer: The Case of Editing in RNA-Binding Motif Protein 8A - Asra Abukar; Martin Wipplinger; Ananya Hariharan; Suna Sun; Manuel Ronner; Marika Sculco; Agata Okonska; Jelena Kresoja-Rakic; Hubert Rehrauer; Weihong Qi; Victor W. van Beusechem; Emanuela Felley-Bosco (Cells, 2021)
Mesothelioma is an aggressive cancer associated with asbestos exposure. RNA-binding motif protein 8a (RBM8A) mRNA editing increases in mouse tissues upon asbestos exposure. The aim of this study was to further characterize the role of RBM8A in mesothelioma and the consequences of its mRNA editing. RBM8A protein expression was higher in mesothelioma compared to mesothelial cells. Silencing RBM8A changed splicing patterns in mesothelial and mesothelioma cells but drastically reduced viability only in mesothelioma cells. In the tissues of asbestos-exposed mice, editing of Rbm8a mRNA was associated with increased protein immunoreactivity, with no change in mRNA levels. Increased adenosine deaminase acting on dsRNA (ADAR)-dependent editing of Alu elements in the RBM8A 3′UTR was observed in mesothelioma cells compared to mesothelial cells. Editing stabilized protein expression. The unedited RBM8A 3′UTR had a stronger interaction with Musashi (MSI) compared to the edited form. The silencing of MSI2 in mesothelioma or overexpression of Adar2 in mesothelial cells resulted in increased RBM8A protein levels. Therefore, ADAR-dependent editing contributes to maintaining elevated RBM8A protein levels in mesothelioma by counteracting MSI2-driven downregulation. A wider implication of this mechanism for the translational control of protein expression is suggested by the editing of similarly structured Alu elements in several other transcripts.